The ldh phylogeny for environmental isolates of Lactococcus lactis is consistent with rRNA genotypes but not with phenotypes. - Urbach, E (1997)
Lactate dehydrogenase (ldh) gene sequences, levels of 16S rRNA group-specific probe binding, and phenotypic characteristics were compared for 45 environmental isolates and four commercial starter strains of Lactococcus lactis to identify evolutionary groups best suited to cheddar cheese manufacture, ldh sequences from the environmental isolates showed high similarity to those from two groups of L. lactis used for industrial fermentations, L. lactis subsp. cremoris and subsp. lactis. Within each phylogenetically defined subspecies, ldh sequence similarities were greater than 99.1%. Strains with phenotypic traits formerly diagnostic for both subspecies were found in each ldh similarity group, but only strains belonging to L. lactis subsp. cremoris by both the newer, genetic and the older, superseded phenotypic criteria were judged potentially suitable for the commercial production of cheddar cheese. Identical evolutionary relationships were inferred from ldh sequences and from binding of subspecies-specific, 16S rRNA-directed oligonucleotide probes. However, groups defined according to these chromosomal traits bore no relationship to patterns of arginine deamination, carbon substrate utilization, or bacteriophage sensitivity, which may be encoded by cryptic genes or sexually transmissible genetic elements. Fourteen new L. lactis subsp. cremoris isolates were identified as suitable candidates for cheddar cheese manufacture, and 10 of these were completely resistant to three different batteries of commercial bacteriophages known to reduce starter activity.